PEMANFAATAN TANAMAN UPAKARA SEBAGAI MEDIA ALAMI DALAM PEMBELAJARAN BIOLOGI DI SEKOLAH - I Gusti Ayu Rai (SEMBIO: Prosiding Seminar Nasional Biologi dan Pendidikan Biologi, 2023)
Learning is a process of educational interaction that occurs between teachers and students, and one of the components that determines its success is learning media. Using appropriate media in learning activities is one way to achieve the learning objectives you want to achieve. The diversity of upakara plants can be used as a natural learning medium in conveying plant biodiversity material in biology learning at school. The use of upakara plants as a learning medium can provide direct experience to students, giving a complete and meaningful impression of various plant variations based on characteristics that can be observed by involving all the five senses. Students not only receive information, but are actively involved in exploring, seeking and discovering new experiences to be able to construct their own knowledge. Therefore, the use of upakara plants found in the surrounding environment acts as a natural medium that can help develop all students' potential in understanding and recognizing the types of plants in nature. Apart from that, students are also able to apply their understanding of the importance of plant biodiversity, as well as apply the principles of grouping living things (taxonomy) based on observable characteristics, so as to facilitate learning activities, especially on plant biodiversity material.